Clinical and laboratory characteristics of occult hepatitis B - E. V. Esaulenko; A. A. Sukhoruk; M. V. Ponyatishina; E. O. Shibaeva; K. A. Zakharov (Журнал инфектологии, 2016)
HBsAg earlier was always considered as the required serological marker of the current HBV-infection, and the presence of НВsAb was considered as evidence of the previous infection with the elimination of virus and the recovery. Exceptions of this rule were discovered more than two decades ago, after which it appeared the concept «occult» hepatitis В.Aim: to characterize clinical course of chronic HBV-infection HBsAg-negative (occult) depending on HBsAb levels in serum.Materials and methods: were examined 198 patients with HBsAg-negative chronic HBV-infection, with the confirmation mono-infection in the absence of factors of liver injury noninfectious etiology.Results: most of the patient was in 45–74 years old. In 53 patients (27,8%) were identified HBcAb and HBsAb titer greater than 10 IU/l: positive HBcAb and HBsAb titre from 10 to 100 IU/l in 21,2% of cases; positive HBcAb and HBsAb titer more than 100 IU/l – 5,5%. DNA HBV was determined in 7,1% of cases. Cirrhotic stage of disease diagnosed in 30,2% of patients with low levels of HBsAb and 13,2% of patients with a high level of HBsAb. Evaluation of the degree of liver cirrhosis were revealed a class C in 86,9% of cases. Patients with decompensated cirrhosis are twice as likely HBsAb in low titre than high.Conclusion: chronic HBV-infection with the serological profile of «past infection» independently of the level HBsAb can estimate as disease with the latent flow and may progression of pathologic process up to cirrhosis of the liver. These patients are subject to regular medical check once a year in a day hospital of a specialized center.